Analisis Faktor - Faktor yang Mempengaruhi Keputusan Pembelian Produk Pada Promo McD Kelapa Gading Jakarta Utara - Prastiwi, Ika; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2023)
Advances in technology encourage people to do activities quickly and practically. One important aspect of modern life is the selection of fast food or drinks. This study aims to determine the effect of purchasing decisions on the McDonald's promo menu and to identify and analyze McDonald's promotional strategies to influence prospective customers' purchases. The method used in this study is a qualitative method by observing and interviewing McDonald's leaders and employees and their customers. The results of the study show that the dominant factors that influence consumers in purchasing products at McDonald's are price and promotion factors. This is indicated by the existence of a promotional strategy carried out with a variety of attractive menus and good and fast service at McDonald's which influences consumer interest in buying McDonald's products.